PENGARUH PELATIHAN DAN DISIPLIN KERJA TERHADAP KINERJA KARYWAN PT. JASA MARGA DI GERBANG TOL CIKAMPEK UTAMA - Jhon Ferry Manullang; Irawan Noor (Jurnal Ekonomi dan Industri, 2020)
To determine the effect of training and work discipline on the performance of employees of PT. Jasa Marga at the Main Cikampek Toll Gate. This research is included in the category of causal associative research using a quantitative approach. The study population was all employees of PT. Jasa Marga who served at the Main Cikampek Toll Gate. This research sampling technique using simple random sampling. This study used a sample size with the Slovin formula. Analysis method with simple and multiple linear regression. The result partially or simultaneous training and work discipline have a positive and significant effect on the performance of employees of PT. Jasa Marga Main Cikampek Toll Gate is good.